New Continuous Laser Emissions in Te 2. Issue 5 (1983) - Topouzkhanian, A.; Wellegehausen, B.; Effantin, C.; d'Incan, J.; Verges, J.
Abstract : New continuous laser emissions of different Te2 isotopes on many lines in the spectral range of 4600 Å to 7800 Å have been obtained upon excitation with the 4067 Å and 4131 Å lines of a krypton ion laser. Thresholds of several mW and output efficiencies of 5% have been achieved. By means of Fourier transform spectrometry accurate fluorescence wavenumbers have been determined, leading to an exact assignment of the observed laser lines.